Associations of combinations of housing tenure status and household structure with subjective happiness among community‐dwelling elderly people: A cross‐sectional study with stratified random sampling. Issue 6 (25th March 2020) - Hidaka, Tomoo; Endo, Shota; Kasuga, Hideaki; Masuishi, Yusuke; Kakamu, Takeyasu; Abe, Koichi; Fukushima, Tetsuhito
Abstract : Aim: Subjective happiness is an important marker of successful aging, and is associated with housing tenure status and household structure. However, the associations between subjective happiness and combinations of housing tenure status and household structure have not yet been clarified. Therefore, we examined which combinations of housing tenure status and household structure are associated with high or low subjective happiness among community‐dwelling elderly people. Methods: Subjects were enrolled by stratified random sampling, and comprised of 1602 elderly persons aged ≥65 years as of January 2017 in Fukushima Prefecture, Japan. The subjects' data were collected via a self‐completed questionnaire (effective response rate: 53.4%), and the associations between subjective happiness and combinations of housing tenure status and household structure were analyzed by chi‐squared test and logistic regression analysis, controlling the confounding variables such as care support needs, subjective economic status and health status. Results: The subjects reported significantly decreased subjective happiness when they were a renter living alone (odds ratio [OR] = 0.427 and 95% confidence interval [CI] = 0.249, 0.732) and with others (OR = 0.420 and 95% CI = 0.256, 0.687) after adjustment for confounding variables, compared with owner‐occupier living with others (referent). Conclusions: The results of the current study revealed significantly decreased subjective happiness when the subjects were renters regardless of household structure. Therefore, housing tenure status may be a stronger determinant of subjective happiness among community‐dwelling elderly people than household structure. Geriatr Gerontol Int 2020; : – .